Gangguan Fungsi Penghidu - Khairani Ayunanda Ikhlas Ikhlas; Effy Huriyati (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2022)
ABSTRACT Introduction: Olfaction is importance as a warning system for environmental hazard such as smoke, leaking natural gas, and spoiled food, so olfactory dysfunction can be fatal. Objectives: To know and understand kind of, pathophysiology, test and management of olfactory dysfunction. Literature: olfactory dysfunction can be anosmia, hyposmia, dysosmia, phantosmia, and parosmia. During this pandemic, olfactory disorders are one of the importance symptomp of corona virus infection. Anamnesis of clinical history smell disorder is importance before psycal examination. Olfactory Assessment can be undertaken using subjective patient report, psychopsycal testing, and electrophysiology or imaging. Management of olfactory dysfunction can be olfactory training, medicamentosa, and surgery according to underlying cause. Conclusion: Olfactory dysfunction caused by various factors, with most common causes being head trauma, respiratory tract infection, and chronic rhinosinusitis. Knowing about olfactory dysfunction and its management is importance to prevent spread of certain viral infection and the fatal condition that can be caused by olfactory dysfunction. Keywords: smell, anosmia, hyposmia, olfactory assessment, corona viral infection